Inclusion of cayenne flour (Hibiscus rosa-sinensis), cajeto (Trichanthera gigantea) and probiotic (Saccharomyces cerevisiae), on the productive parameters and digestibility in broilers (Revista Sistemas de Producción Agroecológicos, 2022)
The development of poultry feeding technologies has improved efficiency, favoring the production process; This evolution has caused balanced food factories to rapidly increase their coverage and cost, which directly affects producers, therefore, the need has been created to look for new, cheaper nutrition alternatives, using available resources such as trees and forage shrubs. The objective of the work was to determine if the replacement of concentrate by two mixed meals: cayenne (Hibiscus rosa-sinensis) and cajeto (Trichanthera gigantea) with and without probiotic (Saccharomyces cerevisiae) in the diet of broilers (WP and WOP respectively) , generates changes in productive parameters and nutrient digestibility; For this, the study was carried out in Villavicencio, Meta, at the Barcelona Farm of the Universidad de los Llanos, with 108 chickens that were fed during the first 15 days with a diet based on commercial balanced starter feed according to the rations indicated for the line. cob 500; Starting on day 16, the diets prepared for this project were supplied, which included commercial balanced feed (CBF) ground to obtain the powdered feed to homogenize it with the cayenne (CYF) and cajeto (CJF) flour, at replacement levels of the 5 and 10% with and without probiotic, as follows; T1: CBF, T3: CBF + 2.5% CYF + 2.5% CJF; T5: CBF + 5% CYF + 5% CJF; all without probiotic (WOP), and T2, T4 and T6 respectively equal to T1, T3 and T5 but adding probiotic (WP). A completely randomized statistical design was implemented, with a factorial arrangement: two levels of probiotic (WP and WOP), three of inclusion of the mixture of cayenne and cajeto flours: (0, 5 and 10%), three replicates per treatment, each with six experimental units. The variables to be evaluated were: digestibility coefficients (DCO) of dry matter (DM), crude protein, fat, non-nitrogenous extract (NNE), crude fiber (CF), neutral detergent fiber (NDF) and acid detergent fiber (FDA). ), total digestible nutrients (TDN), digestible energy (DE) and metabolizable energy (ME), feed intake, weight gain, feed conversion and biological value of protein (VPB); For which, after verifying the normality of the data, an ANOVA was carried out and subsequently the multiple comparison of the mean was carried out with the Duncan Test. The inclusion of (CYF and CJF) with and without probiotic in the diet of broilers under the controlled conditions of the study, showed that the use of probiotic (Saccharomyces cerevisiae) improves productive indicators such as weight gain, final total weight and consumption of food; It should be noted that in the case of feed conversion, variations in the results were observed, showing benefits of the probiotic only for the commercial concentrated treatment WP, added to this, it is observed that the diets of 5 and 10% of CYF and CJF that include the use of probiotic increase the results referring to digestibility coefficients compared to diets that do not include probiotic.
Keywords: poultry; shrubs; trees; supplementation; weight gain